The Error Analysis of Google Translate and Bing Translator in Translating Indonesian Folklore - Jufriadi, Jufriadi; Asokawati, Amalia; Thayyib, Magfirah (FOSTER: Journal of English Language Teaching, 2022)
The objective of this research is to find out the lexical errors made by Google Translate and Bing Translator in translating Indonesian folklore "Princess Tandampalik" and "Sigarlaki and Limbat." The research applied the qualitative method. The data were analyzed using hybrid taxonomy of error analysis from Vilar, et al. The results of this research show that Google Translate made 103 errors in total which consist of 12 missing words, 19 errors in word order, 64 incorrect words, and 8 unknown words. Meanwhile, Bing Translator made 95 errors which consist of 5 missing words, 1 error in word order, 88 incorrect words, and 1 unknown word. Incorrect word is the most frequent error found in the translation resulted from Google Translate and Bing Translator with a total of 152 errors. The incorrect words mainly occurred in the translation of adjectives and adverbs in which Google Translate and Bing Translator mostly translated them into noun form. Thus, it can be concluded that both machine translators' performances are not different because they have their advantages and disadvantages.